Female Rats Are Resistant to Cognitive, Motor and Dopaminergic Deficits in the Reserpine-Induced Progressive Model of Parkinson’s Disease - Lima, Alvaro C.; Meurer, Ywlliane S. R.; Bioni, Vinicius S.; Cunha, Débora M. G.; Gonçalves, Narriman; Lopes-Silva, Leonardo B.; Becegato, Marcela; Soares, Manuela B. L.; Marinho, Gabriela F.; Santos, José R.; Silva, Regina H. (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease (PD) is the second most common neurodegenerative disease. The main symptoms are motor signs such as resting tremor and difficulty in initializing movements. Non-motor alterations, such as cognitive deficits, can precede the motor symptoms. PD is more frequent in men than women. The mechanisms related to this difference are not completely understood. There is evidence that females present distinct characteristics in dopaminergic function compared to males. While the severity of motor impairments is often compared between sexes, little is known about sex differences in the prodromal stage. Most animal models of PD present acute severe motor impairment, which precludes the study of non-motor symptoms. Our research group have proposed an adaptation of the classic reserpine protocol, using low doses in a chronic treatment. This method allows the observation of progressive motor impairment as well as premotor deficits. Here we investigate possible behavioral and neuronal sex differences in the effects of the repeated treatment with a low dose of reserpine in rats. Male and female Wistar rats received 10 to 15 injections of reserpine (0.1mg/kg) or vehicle, on alternate days. We followed-up the estrous cycle phases and conducted motor and cognitive assessments (catalepsy, open field, oral movements and object recognition tests). The euthanasia occurred 48 hours after the 10th or 15th injections, with the collection of blood for the quantification of sex hormones and brains for tyrosine hydroxylase (TH) immunohistochemistry in the substantia nigra pars compact (SNpc). Reserpine induced progressive catalepsy, involuntary oral movements and cognitive deficits in male rats. The behavioral effects of reserpine were attenuated (motor) or absent (cognitive) in females. Reserpine decreased TH immunoreactivity in males, but not in females. Estrogen levels in females negatively correlated with catalepsy duration. Our findings show that females present a delay and/or a prevention in the reserpine-induced motor alterations in the progressive PD model, compatible with the lower prevalence of this disease in women. Further, females were protected from the deficit in object recognition at the prodromal stage. The absence of reserpine-induce decrease in TH immunoreactivity suggests that differences in dopaminergic function/plasticity are related to this protection in female sex.